(5x^2 + 3x ) + ( 2x + 5)

Question

Asked 4/8/2012 7:47:17 PM

Updated 9/18/2016 2:46:08 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by Andrew. [9/18/2016 2:45:08 PM]

s

Boyinbedroom|Points 249|

croix92|Points 60|

Question

Asked 4/8/2012 7:47:17 PM

Updated 9/18/2016 2:46:08 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by Andrew. [9/18/2016 2:45:08 PM]

Rating

8

(5x^2 + 3x ) + ( 2x + 5)

= 5x^2 + 5x + 5

= 5x^2 + 5x + 5

Added 9/18/2016 2:44:59 PM

This answer has been confirmed as correct and helpful.

8

(5x – 5 ) – ( 3x – 3)

= (5x - 5) + (-3x + 3)

= 2x - 2

= (5x - 5) + (-3x + 3)

= 2x - 2

Added 9/18/2016 2:46:08 PM

This answer has been confirmed as correct and helpful.

(12y3 + 9 y2 + 21y) **Weegy:** x+3y=-15
3y=-x-15
y=(-1/3)x-5 **User:** (10x2 – 14x – 12) ÷ (5x + 3) **Weegy:** x=2 **User:** (4x + 1 )(x2 – 9x + 5) **Weegy:** Best Answer - Chosen by Voters
((4/x) - (2/4x)) / ((1/2x) + (3/2x))
= ((16/4x) - (2/4x))/(4/2x)
= (14/4x)/(2/x)
= (14/4x) * (x/2)
= 14x/8x
= 14/8
= 7/4
(More)

Question

Updated 6/4/2014 8:21:17 AM

2 Answers/Comments

12y^3 + 9 y^2 + 21y = 3y(4y^2 + 3y + 7)

Added 6/4/2014 8:18:13 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/5/2014 4:12:40 AM]

(10x^2 – 14x – 12) ÷ (5x + 3)

= (5x + 3)(2x - 4)/(5x + 3)

= 2x - 4

= (5x + 3)(2x - 4)/(5x + 3)

= 2x - 4

Added 6/4/2014 8:21:09 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/5/2014 4:13:07 AM]

5x+2x^2+8x+34+8x+12x=

Question

Not Answered

Updated 7/16/2014 2:02:29 AM

1 Answer/Comment

5x+2x^2+8x+34+8x+12x=2x^2+33x+34

Added 7/16/2014 2:02:29 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:18:12 AM]

(5x – 5 ) – ( 3x – 3) **Weegy:** is equal to 8x **User:** (8x – 2) + (7x + 6) **User:** (4x – 3.5) – (3x + 1.7) **Weegy:** First, get rid of the parenthese, 4x-3.5-3x-1.7 Second, Subtraction, x-5.2. x-5.2x is the answer. **User:** (12y3 + 9 y2 + 21y) ÷ 3y **Weegy:** x+3y=-15
3y=-x-15
y=(-1/3)x-5 (More)

Question

Updated 9/5/2014 4:11:57 AM

4 Answers/Comments

(5x – 5 ) – ( 3x – 3)

= (5x - 5) + (-3x + 3)

= 2x - 2

= (5x - 5) + (-3x + 3)

= 2x - 2

Added 9/5/2014 4:09:25 AM

This answer has been confirmed as correct and helpful.

(8x – 2) + (7x + 6) = 15x + 4

Added 9/5/2014 4:09:41 AM

This answer has been confirmed as correct and helpful.

(4x – 3.5) – (3x + 1.7)

= (4x - 3.5) + (-3x - 1.7)

= x - 5.2

= (4x - 3.5) + (-3x - 1.7)

= x - 5.2

Added 9/5/2014 4:10:06 AM

This answer has been confirmed as correct and helpful.

(12y^3 + 9y^2 + 21y) ÷ (3y)

= (12y^3/3y) + (9y^2/3y) + (21y/3y)

= 4y^2 + 3y + 7

= (12y^3/3y) + (9y^2/3y) + (21y/3y)

= 4y^2 + 3y + 7

Added 9/5/2014 4:11:57 AM

This answer has been confirmed as correct and helpful.

33,363,181

questions answered

There are no comments.